Experimental Investigation on the Stress-Dependent Permeability of Intact and Fractured Shale - Yongxiang Zheng; Jianjun Liu; Yichen Liu; Di Shi; Bohu Zhang (Geofluids)
The permeability of shale is extremely low. Therefore, the shale reservoir needs fracturing. The fracture network by fracturing can increase the permeability in a stimulated shale reservoir. To understand the permeability evolution in the stimulated shale reservoir, this study measured the permeability of intact and fractured shale samples with different pore pressure and confining pressure by the transient pulse test. And the differences between the two kinds of samples in permeability were analyzed. The results show that permeability magnitude of fractured shale is increased by 5 orders compared to the intact shale. It means that fracture networks after fracturing can effectively improve the permeability. Besides, the change in matrix permeability is the result of the combined effect of slippage effect and matrix deformation. At low pore pressure, the influence of slippage effect is more significant. Based on the results, an improved exponential function was established to describe the relationship between permeability and effective stress of shale matrix. Moreover, the permeability of fractured shale is still bigger than that of the shale matrix when the confining pressure is larger than pore pressure. This paper provides theoretical guidance for studying the evolution of reservoir permeability before and after fracturing.